Congenital fibropapillomatosis in a pig - Schwertz, Lara Cristine; Miglioranza, Débora; Schwertz, Claiton Ismael; Gabriel, Mateus Eloir; Mori, Ademar Masaaki; Baldi, Kelen Regina Ascoli; Driemeier, David; Mendes, Ricardo Evandro; Gomes, Teane Milagres Augusto (Brazilian Journal of Veterinary Pathology, 2023)
This paper reports a case of congenital cutaneous fibropapillomatosis in a piglet from a swine-producing farm in the municipality of Concórdia, Santa Catarina - Brazil. The main gross lesion was an exophytic mass with a light pink color, irregular surface, and margins, sometimes with a cerebrum-like appearance, extending from the right cervical and scapular regions to the craniomedial portion of the right forelimb. Histologically, the mass consisted of a well-delimited proliferation of fibrous tissue in the superficial dermis, covered by a proliferation of keratinocytes with low cellular atypia. Diffuse and severe hyperkeratosis of the epidermis was also observed. Immunohistochemistry for papillomavirus was negative, indicating that this animal had spontaneous non-viral papillomatosis. This condition is rare in pigs, with only two other cases described in the literature.